1995
DOI: 10.1007/s002040050214
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of water soluble aluminium chloride in the hippocampus after transdermal uptake in mice

Abstract: Normally, only very small amounts of ingested aluminium are absorbed and accumulated. Despite the percutaneous absorption of many drugs and chemicals, the skin has not been considered as a possible site at which aluminium could enter the body. Application of low aqueous concentrations of aluminium chloride (A1C1(3), 6H20) (0.025-0.1 micrograms/cm2) to healthy shaved Swiss mouse skin for 130 days led to a significant increase in urine, serum and whole brain aluminium, especially in the hippocampus, compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 14 publications
0
25
0
1
Order By: Relevance
“…Aluminium is absorbed through the human (Flarend et al, 2001;Guillard et al, 2004) and mouse (Anane et al, 1995(Anane et al, , 1997 skin, and it is conceivable that the daily application of antiperspirants, containing high concentrations of aluminium, Figure 5. AlCl 3 is not detectably mutagenic in bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aluminium is absorbed through the human (Flarend et al, 2001;Guillard et al, 2004) and mouse (Anane et al, 1995(Anane et al, , 1997 skin, and it is conceivable that the daily application of antiperspirants, containing high concentrations of aluminium, Figure 5. AlCl 3 is not detectably mutagenic in bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In aqueous solutions at pH 7.0, both aluminium chloride and aluminium chlorohydrate yield aluminium hydroxide and they are absorbed through human and mouse skin (Flarend et al, 2001;Guillard et al, 2004;Anane et al, 1995Anane et al, , 1997. Transdermal uptake of aluminium contained in antiperspirants is not the only route by which this element accumulates in the body, aluminiumbased compounds being found in pharmaceuticals, food additives and various household products (Krewski et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The skin is no barrier to aluminium absorption (Exley, 1998). Experiments with shaved adult mice, naked mouse pups and excised skin patches taken from adult mice have all shown that topically applied aluminium salts can be absorbed through mouse skin (Anane et al, 1995(Anane et al, , 1997. Furthermore, dermal absorption of aluminium could be detected in human subjects from a single application of aluminium chlorhydrate using the isotope 26 Al as the tracer (Flarend et al, 2001).…”
Section: Agents That Damage Dnamentioning
confidence: 99%
“…All the samples have undergone the necessary treatment before heavy metals analysis by electrothermal atomic absorption spectrophotometer according to the method described in (Anane et al, 1995;Vaidya and Rantala, 1996). For each sample, there were 3 replicates and the average values and standard deviation were calculated.…”
Section: Processing and Analysismentioning
confidence: 99%